Asylum in the twenty-first century: Trends and challenges - Atak, Idil; Crépeau, François (Routledge Handbook of Immigration and Refugee Studies, 2022)
A political practice and institution found in most civilisations throughout history, asylum in the twenty-first century finds itself in a tumultuous period. The 1951 Refugee Convention regime endures, but many States are trying hard to prevent asylum-seekers from reaching their borders. With refugee resettlement stuck at one per cent of the needs, it is no wonder that refugees finding no other solution to build a future for their family will resort to other means to reach places where they can hope to thrive. Destination States are deploying multiple strategies to avoid being responsible for thousands of refugees. They have thus considerably strengthened their ‘fight’ against undocumented migration and are criminalising asylum-seekers through importing into administrative law concepts and institutions of criminal law, while some have adopted deterrence tactics or implemented ‘externalisation strategies’. They also have devalued the principle of non-refoulement, either through directly refouling or through use of tactics resulting in refoulement. Asylum-seekers are also subjected to biometric identifiers stored in databases interconnected with multiple other databases, nationally and internationally. This chapter explores global trends and challenges in asylum in the twenty-first century and outlines main approaches in the field.